2015
DOI: 10.1007/s00228-015-2000-2
|View full text |Cite
|
Sign up to set email alerts
|

Improved participants’ understanding in a healthy volunteer study using the SIDCER informed consent form: a randomized-controlled study

Abstract: PurposeThis study aimed to evaluate the applicability of the principles and informed consent form (ICF) template proposed by the Strategic Initiative for Developing Capacity in Ethical Review (SIDCER) in a clinical pharmacokinetic study by comparing the volunteers’ understanding of the enhanced ICF (developed based on the SIDCER methodology) and the conventional ICF (which was previously approved by local Ethics Committee and used in the clinical study).MethodsA total of 550 volunteers were randomly assigned t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
1
9
1
Order By: Relevance
“…The SIDCER ICF was found to be superior to the conventional ICF in improving parental understanding of several elements of the ICF content. The overall results of this study are consistent with three previous informed consent studies that exhibited the improvement of participants’ understanding by the SIDCER ICF 17 19 20. In line with a recent integrative review on informed consent, it is reasonable to assume that the evidence of improved participants’ understanding by the SIDCER ICF is largely attributable to its simplicity and concise format with increased processability (using summary boxes, highlights and illustrations, when appropriate) 23…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The SIDCER ICF was found to be superior to the conventional ICF in improving parental understanding of several elements of the ICF content. The overall results of this study are consistent with three previous informed consent studies that exhibited the improvement of participants’ understanding by the SIDCER ICF 17 19 20. In line with a recent integrative review on informed consent, it is reasonable to assume that the evidence of improved participants’ understanding by the SIDCER ICF is largely attributable to its simplicity and concise format with increased processability (using summary boxes, highlights and illustrations, when appropriate) 23…”
Section: Discussionsupporting
confidence: 88%
“…This ICF study planned to enrol 210 parents (with 105 parents in each arm), based on an a priori estimate to detect the hypothesised effect size of 20% difference between two independent proportions of the primary endpoint ( p 1 =0.8 and p 2 =0.6), with the precision and confidence level of 95%, 80% power and allocation ratio of 1, with a continuity correction. This hypothesised effect size was based on the findings in our previous study 19…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Developing a consent process with the right amount of information for sufficient understanding continues to be a challenge for researchers, especially with complex study designs. Several methods have been designed to adapt the consent process to specific contexts using, for example, an enhanced consent process that reduces the amount of information presented while maintaining international regulations [3] or rapid ethical assessments prior to development of specific consent processes [4,5]. In a recent review, Gillies (2018) synthesized papers that focused on patient reported measures of consent in clinical trials and found that the majority of measures focused on understanding, not the myriad factors that influence participation, such as decision-making mechanisms [6].…”
Section: Introductionmentioning
confidence: 99%
“…Clients should give their consent voluntarily and should not be impelled to do so. Patients should have a real understanding of the risks that would be involved in their treatment process [16].…”
Section: Who Should Obtain Inform Consent From Patient?mentioning
confidence: 99%